Are we ready for climate-friendly inhaler prescription and usage? A qualitative study among primary and secondary care patients, healthcare professionals and healthcare insurers in the Netherlands - Rianne M J J van der Kleij; Berdien Oosterveld; Johanna M C Broese; Hans Ossebaard (BMJ Open, 2025)
Objectives This study explored the knowledge and awareness of Dutch patients, healthcare professionals (HCPs) and healthcare insurers on the climate impact of inhalers as well as (factors influencing) their attitude towards climate-friendly inhaler prescription.Design/setting We recruited participants for this qualitative study with purposive sampling. We conducted four online focus groups with patients, six with HCPs and two interviews with healthcare insurer representatives. Determinants were analysed with the Framework Approach.Participants 21 patients, 27 HCPs and two healthcare insurer representatives.Results Knowledge and awareness on the climate impact of inhalers varied and was generally lower among patients and healthcare insurers than among HCPs. The attitude towards climate-friendly inhaler prescription was variable among patients and mainly positive among HCPs. Both patients and HCPs assigned a greater role to HCPs than to patients in considering climate impact and agreed that patients’ interest must remain paramount. Factors influencing implementation were mainly related to outcome expectancies, such as expected effect on freedom of choice, expected response of patients and expected effect on patients’ health. The latter is partly influenced by beliefs about different types of inhalers. HCPs expressed a need for information and training on the topic and for collaboration with other stakeholders in the field of pulmonary care. Healthcare insurers assign themselves a role in a more climate-friendly healthcare but are reluctant to direct the preference policy on climate impact.Conclusions Both patients and HCPs feel climate-friendly inhaler prescription is important. Implementation can be promoted by enhancing awareness and providing HCPs with information on inhaler climate impact, how to safely practice climate-friendly prescription and how to inform patients about its benefits. Both patients and HCPs emphasise the significance of preserving freedom of choice in prescription and highlight the need for a consensus approach on climate-friendly prescribing endorsed by all pulmonary care stakeholders.